Effect of nanochitosan-iodine application in lettuce on biofortification, growth and yield - Treviño-Ruiz, Karla Stephanie; Ortega-Ortiz, Hortensia; Benavides-Mendoza, Adalberto; González-Morales, Susana (Ecosistemas y Recursos Agropecuarios, 2024)
Iodine (I) is an essential element in human nutrition, however, in plants it is considered a beneficial element. The objective of the present work was to evaluate the application of nanochitosan-iodine complexes (NPsCs-I) on the biofortification of I in lettuce, in addition to its effect on growth and yield. Foliar application of NPsCs-I complexes was carried out on lettuce plants where plant height, head diameter, dry biomass and I content were measured. The application of NPsCs-I complexes had a significant effect on the yienld, since with the application of the complex at a dose of 5 mg L-1 of KIO3, it increased by 30.8% compared to the control. The foliar application of NPsCs-I complexes can provide an alternative for biofortification of I and biostimulation of lettuce plants.
Keywords: Biofortification; biopolymers; nanotechnology; potassium iodate; potassium iodide